Beam Tracing with Refraction - SIKORA, Marjan; MATELJAN, Ivo; BOGUNOVIĆ, Nikola (Archives of Acoustics, 2013)
This paper presents the beam tracing with refraction method, developed to examine the possibil-ity of creating the beam tracing simulation of sound propagation in environments with piecewise non-homogenous media. The beam tracing with refraction method (BTR) is developed as an adaptive beamtracing method that simulates not only the reflection but also the refraction of sound. The scattering andthe diffraction of sound are not simulated. The BTR employs 2D and 3D topology in order to efficientlysimulate scenes containing non-convex media. After the beam tracing is done all beams are stored in abeam tree and kept in the computer memory. The level of sound intensity at the beginning of each beamis also memorized. This beam data structure enables fast recalculation of results for stationary sourceand geometry. The BTR was compared with two commercial ray tracing simulations, to check the speedof BTR algorithms. This comparison demonstrated that the BTR has a performance similar to state-of-the-art room-acoustics simulations. To check the ability to simulate refraction, the BTR was comparedwith a commercial Finite Elements Method (FEM) simulation. In this comparison the BTR simulatedthe focusing of the ultrasound with an acoustic lens, with good accuracy and excellent performance.